STUDY OF GONADOSOMATIC INDEX AND FECUNDITY OF FISH CIRRHINUS MRIGALA (HAMILTON) - V. R. CHAVAN; D. V. MULEY (The Bioscan, 2014)
The major Indian carp Cirrhinus mrigala from Kalambe reservoir near Kolhapur (Maharashtra) was studied from a period of June 2012 to May 2013 to evaluate the gonadosomatic index (GSI). Fecundity of the fish was studied for a period of three months (June to August 2012). The minimum GSI values in both male and female were observed in winter (0.0812 and 0.0857) while maximum of it was estimated in mansoon (1.7200 and 20.5700). It has been observed that fecundity increases with increase in length, body weight and gonad weight of the fish. The species is a moderately fecund, total spawner and having a restricted breeding season.